WANPRESTASI PANITIA DALAM KONTRAK PEMBAYARAN WASIT PADA EVENT JUSTITIA FUTSAL DI KOTA PONTIANAK - NIM. A1011161173, WAN GEHARDO (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstrac Implementation of the agreement between Referee Services and the Justitia Futsal Event committee as a service user which in civil law is included in the type of agreement to perform certain services. The agreement between the Referee Services and the Justitia Futsal Event committee is made in writing. The agreement creates rights and obligations for the parties, because the agreement has fulfilled the legal requirements of the agreement set forth in Article 1320 of the Civil Code, namely the agreement of those who bind themselves, the ability to make or say an agreement, a certain thing and a certain thing. lawful reason.This thesis is according to the formulation of the problem: